1988
DOI: 10.1177/001872678804101004
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of Injustice in a Black Community: Dimensions and Variation

Abstract: Few studies have examined beliefs and attitudes about injustice and discrimination within minority communities. Most research has emphasized the institutional consequences of discrimination, or the racial beliefs of the majority groups. In this study we examine attitudes about injustice and reactions to discriminatory acts within a Black community in the U.S. South. Beliefs and attitudes were found to cluster in three dimensions, including responses to personal discrimination, perceptions of political structur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

1993
1993
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 16 publications
0
19
0
Order By: Relevance
“…Perceptions of individual, cultural and collective/institutional racism were regressed separately on the diversity indices for school and neighborhood. Because research has found that demographic characteristics and psychological well-being are associated with perceptions of discrimination (e.g., Adams and Dressler 1988; Kessler et al 1999), all analyses control for age, gender, parental marital status, parental educational level, self-esteem, depressive symptoms, and life satisfaction (Table 2). The results indicated that more diversity in a student’s school was associated with increased perceptions of cultural racism (column 2).…”
Section: Resultsmentioning
confidence: 99%
“…Perceptions of individual, cultural and collective/institutional racism were regressed separately on the diversity indices for school and neighborhood. Because research has found that demographic characteristics and psychological well-being are associated with perceptions of discrimination (e.g., Adams and Dressler 1988; Kessler et al 1999), all analyses control for age, gender, parental marital status, parental educational level, self-esteem, depressive symptoms, and life satisfaction (Table 2). The results indicated that more diversity in a student’s school was associated with increased perceptions of cultural racism (column 2).…”
Section: Resultsmentioning
confidence: 99%
“…In past years, theoretical attention and empirical work has focused predominantly on whites' racial attitudes and values, with little attention to these factors within minority groups. Only within the past decade or so have many researchers turned their attention to aspects of blacks' racial attitudes, investigating issues such as racial identity attitudes of blacks (Hughes & Hertel, 1990; V. Thompson, 1991), and blacks' mistrust of whites and of major societal institutions (Adams & Dressler, 1988;Terrell & Terrell, 1981;C. Thompson, Neville, Weathers, Poston, & Atkinson, 1990;Watkins & Terrell, 1988).…”
Section: Racial Attitudes Of Blacksmentioning
confidence: 99%
“…Adams and Dressier (1988, p. 762) found that even within a single southem African-American community, and even when dealing with a salient issue like discrimination, "an asstimption of uniformity cannot be made." However, even while acknowledging a lack of uniformity, Adams and Dressier (1988) found that some generalizations could be made about how African Americans view racism; for example, there is a cultural belief system within the African-American community they studieid that places racism within "white culture. "…”
Section: Previous Researchmentioning
confidence: 99%